1979
DOI: 10.1159/000250684
|View full text |Cite
|
Sign up to set email alerts
|

Les actinomycétales en pathologie cutanée

Abstract: After discussing the classification of the Actinomycétales, the authors give a detailed description of the epidemiology and particularly of the clinical features of cutaneous diseases induced by genera such as Actinomyces, Norcardia and Streptomyces. Histopathological and immunological studies, together with laboratory and differential diagnostics, are also examined. In the last section, present therapeutic treatments are briefly outlined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
1983
1983

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Mahgoub (S), Aceves-Ortega (1) and Kamalam and Thambiah (4) claimed good results in several cases they observed. However, Zina et al (8) state that it is difficult to treat actinomycetoma medically. Escudero Gil et al (3) reported clinical resistance to oral ketoconazole therapy and this was in direct contrast to the sensitivity of the pathogenic agent (Madurella grisea) to this antibiotic in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Mahgoub (S), Aceves-Ortega (1) and Kamalam and Thambiah (4) claimed good results in several cases they observed. However, Zina et al (8) state that it is difficult to treat actinomycetoma medically. Escudero Gil et al (3) reported clinical resistance to oral ketoconazole therapy and this was in direct contrast to the sensitivity of the pathogenic agent (Madurella grisea) to this antibiotic in vitro.…”
Section: Discussionmentioning
confidence: 99%